Moran Brothers Co. shipyard near Pioneer Square, Seattle, March 1904 - Romans Photographic Company
After working on ships for a number of years Robert Moran (1857-1943) opened a marine repair shop at Yesler's Wharf in 1882. Shortly thereafter he established Moran Brothers Marine and Sawmill Machinery Company (later Moran Brothers Company) with his brothers, Frank Moran (1860-1934) and Sherman Moran (1865-1929). The firm built steamers and barges for miners on the Yukon River, as well as many large steel and wood vessels, including the battleship USS Nebraska for the U. S. Navy. This image of the Moran Brothers shipyard, located at the foot of South Charles Street south of Pioneer Square, highlights Seattle's busy waterfront. The view is facing north, with Elliott Bay spreading out to the west. In the distance Queen Anne Hill is visible on the right edge of the frame, and Magnolia on the left. 1 photographic print mounted on cardboard; b&w; 7.75 x 9.75 in.